A clinical study of risk factors for acute severe asthma in children - A., Pragalatha Kumar; Gowdra, Aruna; Pise, Dattatreya (International Journal of Contemporary Pediatrics, 2018)
Background: Asthma is one of the most prevalent diseases worldwide with an estimated 300 million affected children. Acute severe asthma in children is one of the common causes of emergency admissions. There is no much study regarding the risk factors for acute severe asthma in children in India. Hence the present study was conducted to know the risk factors for acute severe asthma in children. Methods: A prospective observational study of 100 children between the age group of 5 and 18 years who presented with symptoms and signs of acute severe asthma admitted to the pediatric intensive care unit (PICU) of Indira Gandhi Institute of Child Health (IGICH) for a period of 12 months between January 2015 to December 2015 formed the study group. These children were evaluated for the risk factors responsible for acute severe asthma. Results: A total of 100 children with acute severe asthma were enrolled in the study. The predominant age group was between 5-10 years (68%), the risk factors responsible for acute severe asthma were poor drug compliance (68%), which was statistically significant (p-value <0.0001), exposure to house dust (61%) and smoke (42%) (p <0.0001). There was also marked rise in absolute eosinophil count (62%). Conclusions: Acute severe asthma in children is one of the common causes of emergency admissions. The present study has shown that poor drug compliance, exposure to house dust and smoke were significant risk factors for acute severe asthma.